Danantara Effects on IDXESGL Stock Investment Strategies Using Single Index Model and VaR-Adjusted Sharpe Ratio - Risky Gunawan; Evy Sulistianingsih; Shantika Martha; Yundari Yundari; Fida Fathiyah Addini (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
Danantara, established as Indonesia’s sovereign wealth fund on February 24, 2025, has introduced new dynamics in the Indonesian capital market. This study examines differences in portfolio strategies among IDX ESG Leaders (IDXESGL) index between the pre- and post-Danantara periods by comparing stock composition with positive expected returns and portfolio performance across two periods using the Single Index Model (SIM) and the Value at Risk-Adjusted Sharpe Ratio (VaRSR). The analysis employs an integrated framework that combines SIM for identifying best-performing stocks, a portfolio combination approach, and performance evaluation using the Sharpe ratio and VaRSR. This study utilized daily closing price data covering August 23, 2024, to February 23, 2025, as the pre-Danantara period, and February 24, 2025, to August 24, 2025, as the post-Danantara period. The results indicate that prior to Danantara’s establishment, optimal portfolios were dominated by digital-sector stocks, with higher performance than in the post-Danantara period. In contrast, the post-Danantara period is associated with greater exposure to conglomerates and state-owned enterprises with stronger fundamentals and lower downside risk. Overall, the findings suggest that the VaRSR yields a more conservative performance assessment and highlights a potential reorientation in investment strategies toward stability and resilience following Danantara’s establishment.